Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006459.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for peripheral nerve blockade

Abstract: In experienced hands, ultrasound provides at least as good success rates as other methods of peripheral nerve location. Individual studies have demonstrated that ultrasound may reduce complication rates and improve quality, performance time, and time to onset of blocks. Due to wide variations in study outcomes we chose not to combine the studies in our analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 32 publications
1
59
0
3
Order By: Relevance
“…Another systematic review of 16 RCTs found that use of ultrasound for upper and lower extremity nerve blocks was associated with a better quality of block [11]. Although we did not assess for outcomes other than block success, other authors have noted that the use of ultrasound for nerve blocks is associated with significantly less time to perform blocks, faster onset and longer duration of analgesia, and decreased the risk of vascular puncture or hematoma formation during the block procedure [10][11][12].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another systematic review of 16 RCTs found that use of ultrasound for upper and lower extremity nerve blocks was associated with a better quality of block [11]. Although we did not assess for outcomes other than block success, other authors have noted that the use of ultrasound for nerve blocks is associated with significantly less time to perform blocks, faster onset and longer duration of analgesia, and decreased the risk of vascular puncture or hematoma formation during the block procedure [10][11][12].…”
Section: Discussionmentioning
confidence: 97%
“…Although the superior visualization and localization for injection of local anesthetic provided by ultrasound guidance theoretically would result in a reduction in complication rates (eg, neurologic injuries), this has not been definitively proven [6,7]. Previous reviews and metaanalyses indicate that ultrasound-guided regional anesthesia may offer many benefits including a higher block success rate, decreased time to onset of blocks, and possibly improved quality of sensory block [8][9][10][11][12]. However, these meta-analyses have not examined the analgesic efficacy of ultrasound guidance for specific peripheral nerve blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Complications from femoral nerve blockade are infrequent and are likely decreased with the utilization of point-of-care ultrasound needle guidance. 18,[21][22][23] Needle insertion using the in-plane technique may be superior to "out-of-plane" technique because it allows for improved visualization of the needle tip, avoiding inadvertent injection into the femoral nerve as well as allowing for localization of anesthetic around the target nerve. 2,21,24 Hematoma formation may result from vascular puncture or from bleeding if lymph nodes are penetrated.…”
Section: Pitfall and Complicationmentioning
confidence: 99%
“…Ultraschallgesteuerte Punktionstechniken, die in unserer Abteilung seit 2007 routinemäßig zum Einsatz kommen, scheinen die Sicherheit des Verfahrens dabei noch weiter zu erhöhen [17,18].…”
Section: Diskussionunclassified